“They Are Our Children”: An Examination of Faith-Based, Tuition-Free, Private Schools as Potential Sites of Educational Opportunity for Refugee Children in Egypt and Lebanon - Sally Wesley Bonet; Samira Nabil Chatila (Social Sciences)
(1) Background: Turning the lens away from national schooling, which has long been proven problematic for refugee populations, this comparative case study explores the educational opportunities that faith-based, tuition-free schools provide refugee youth living in protracted exile in low and middle-income neighboring countries. (2) Methods: Leveraging Shirazi and Jaffe-Walter’s concept of countertopography and Bartlett and Vavrus’s comparative case study, this article draws on ethnographic engagement (2017–2019) at “Cairo Christian Academy”, a Sudanese refugee school in Egypt, and qualitative interviews with teachers, administrators, and staff at “Beirut Covenant School” (2020–2021) in Lebanon to answer the following question: What is possible within private, faith-based, tuition-free schools—particularly schools that teach secular curricula and are open to children from all faith backgrounds, as these mirror some of the more egalitarian aspects of public education—which have absorbed refugee students as a part of their mission to care for others? (3) Results and conclusions: Our findings suggest that the funding structures, hiring practices, and moral underpinnings of these schools facilitate caring, loving environments for refugee youth while also providing educational opportunities unavailable to them otherwise in these host countries. Furthermore, our methodological approach explores ways to conduct research in contexts mired in multiple, overlapping crises.